Perancangan Manajemen Proyek Pada Sistem Informasi Sekolah SMA Negeri 1 Tarumajaya Berbasis Website - Dwipa Handayani; Ayu Diah Rositawati; Caroline Julyana Magdalena S.; Deo Pratama Putra; Fransisco Leo Sinema Gea; Nur Afifah; Rahelliana Tinambunan; Rahma Vadilla; Santi Noviyanti; Verdi Ganda Manalu (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2025)
The advancement of information technology has significantly impacted the education sector, including SMA Negeri 1 Tarumajaya, which faces challenges in managing academic and administrative data manually. These manual processes are time-consuming and prone to errors. To address this, a web-based School Information System was developed to enhance administrative efficiency, information transparency, and communication among the school, students, teachers, and parents. The system is designed to manage academic and non-academic data, such as attendance, grades, schedules, and real-time reports, accessible across various devices. Implemented within 4 months and 2 weeks with an efficient budget, the system successfully transformed manual processes into faster, more effective, and less error-prone workflows. The results demonstrate that the system not only improved operational efficiency and data transparency but also strengthened communication between the school and parents, marking a significant step toward educational digitalization.